Attitude and use of contraceptive methods in obstetrics students at the Scientific University of Peru - Iquitos; 2015 - Rios-Rios, Evelyn (2023)
Introduction: Sexuality is part of life, from birth and throughout our existence. The WHO states that it is our right to have gratifying and enriching sexual relations, without coercion and without fear of infections or unwanted pregnancies. Objective: To determine the relationship between Attitude and the Use of Contraceptive Methods in Obstetrics students at the Scientific University of Peru-Iquitos. Materials and Methods: Quantitative study of descriptive, cross-sectional, prospective correlational design, surveying 140 female students out of the 219 who were enrolled in the 2015-1 academic semester. Results: 50.7% (n=71) were between 17 and 19 years of age, 87.9% (n=123) are single; and more than 55.0% are between the I to the IV study cycle. 57.9% (n=81) of the students have an adequate attitude towards contraceptive methods; and 51.4% (n=72) have adequate use of contraceptive methods. The adequate attitude towards contraceptive methods was related to the older age of the students (p=0.002), being married (p=0.006) and a longer study cycle (p<0.001). The adequate use of contraceptives was related to the older age of the students (p=0.029); married women and those with a higher level of study had a higher frequency of adequate use of contraceptives, but this trend was not significant (p>0.05). The students with adequate attitude about contraceptive methods have significantly (p=0.007) an adequate use of contraceptive methods. Conclusions: The adequate attitude about contraceptive methods determines an adequate use of contraceptive methods.